CDK6 is activated by the atypical cyclin I to promote E2F‐mediated gene expression and cancer cell proliferation - Eva Quandt; Núria Masip; Sara Hernández‐Ortega; Abril Sánchez‐Botet; Laura Gasa; Ainhoa Fernández‐Elorduy; Sara Plutta; Joan Marc Martínez‐Láinez; Samuel Bru; Pau M. Munoz‐Torres; Martin Floor; Jordi Villà‐Freixa; et al. (Molecular Oncology, 2023)
Cyclin‐dependent kinases (CDKs), together with their cyclin partners, are the master cell cycle regulators. Remarkably, the cyclin family was extended to include atypical cyclins, characterized by distinctive structural features, but their partner CDKs remain elusive. Here, we conducted a yeast two‐hybrid screen to identify new atypical cyclin–CDK complexes. We identified 10 new complexes, including a complex between CDK6 and cyclin I (CCNI), which was found to be active against retinoblastoma protein. CCNI upregulation increased the proliferation of breast cancer cells in vitro and in vivo, with a magnitude similar to that seen upon cyclin D upregulation, an effect that was abrogated by CDK6 silencing or palbociclib treatment. In line with these findings, CCNI downregulation led to a decrease in cell number and a reduction in the percentage of cells reaching S phase. Finally, CCNI upregulation correlated with the high expression of E2F target genes in large panels of cancer cell lines and tissue samples from breast cancer patients. In conclusion, we unveil CCNI as a new player in the pathways that activate CDK6, enriching the wiring of cell cycle control.